The cluster system of the Large Magellanic Cloud. - Kontizas, M.; Morgan, D. H.; Hatzidimitriou, D.; Kontizas, E. (1990)
A new catalogue of clusters in the Large Magellanic Cloud has been constructed from searches of the IIIa-J component of the ESO/SERC Southern Sky Atlas. The catalogue contains coordinate and diameter measurements of 1762 clusters in a 25^deg^ x 25^deg^ area of sky centred on the LMC, but excluding the very crowded 3.5 deg^2^ region around the Bar. The distribution of there clusters appears as two superimposed elliptical systems. The higher density inner system extends over ~ 8^deg^; the lower density outer system can be represented by a 13^deg^ x 10^deg^ disc inclined at 42^deg^ to the line of sight. There are suggestions of two weak "arms" in the latter.
Keywords: Astronomical Catalogs; Astronomy; Line Of Sight; Magellanic Clouds; Photographic Plates; Schmidt Telescopes; Southern Sky; star clusters; Star formation